SARS-CoV-2 pandemic and epilepsy: The impact on emergency department attendances for seizures. (November 2020) - Cheli, Marta; Dinoto, Alessandro; Olivo, Sasha; Tomaselli, Marinella; Stokelj, David; Cominotto, Franco; Brigo, Francesco; Manganotti, Paolo
Abstract: Introduction: The risk of acquiring SARS-CoV-2 in a hospital setting and the need of reorganizing the Emergency Departments (EDs) to cope with infected patients have led to a reduction of ED attendances for non-infectious acute conditions and to a different management of chronic disorders. Methods: We performed a retrospective study evaluating the frequency and features of ED attendances for seizures during the lockdown period (March 10th–April 30th 2020) in the University Hospital of Trieste, Italy. We studied the possible pandemic impact on the way patients with seizures sought for medical assistance by comparing the lockdown period to a matched period in 2019 and to a period of identical length preceding the lockdown (January 18th–March 9th 2020). Results: A striking decrease in total ED attendances was observed during lockdown (4664) compared to the matched control (10424) and to the pre-lockdown (9522) periods. A similar reduction, although to a lesser extent, was detected for seizure attendances to the ED: there were 37 during lockdown and 63 and 44 respectively during the two other periods. Intriguingly, during the lockdown a higher number of patients attended the ED with first seizures (p = 0.013), and more EEGs (p = 0.008) and CT brain scans (p = 0.018) were performed; there was a trend towards more frequent transport to the ED by ambulance (p = 0.061) in the lockdown period. Conclusions: Our data suggest that the pandemic has affected the way patients with seizures access the Health Care System.